Website Information System Design With SEO Techniques (Search Engine Optimization) - Syaiful Bahri; Doni El Rezen Purba (INFOKUM, 2021)
The development of website technology is currently very fast, so it is very easy to get accurate information. Promotion through the website is also currently one of the things that digital marketers are interested in. A good website will have a good impact on the goods we produce. One of the good or bad of a website is determined by SEO (Search Engine Optimization) techniques. In this study, we use the website www. webkuliah.com to prove whether SEO techniques can have a good impact on search results on search engines such as Google, Yahoo, or bing. The results obtained prove that SEO is very good in making websites known by search engines. The results prove that by using the keyword web university on the Bing search engine, the website can occupy the first page of Bing, it's just that it doesn't rank number 1 because it can't compete with the campus domain, which happens to be the name of the website used similar to the name of the campus. But the drawback of this SEO technique is that it takes a long time to occupy the first page of Google because this service is free.